Efektivitas Layanan Informasi Dengan Menggunakan Film Imperfect Untuk Mereduksi Self Harm Pada Diri Mahasiswa : - Indah, Maulina; Maghfirotul Lathifah (Efektor, 2021)
This study aims to determine the effectiveness of information services using imperfect films to reduce self harm to students. This research approach is quantitative. This research is a type of pre-experimental research design, one group pre-test post-test design. This study has two variables, namely the dependent variable or variable X (information services with imperfect film media) and also the independent variable or variable Y (self harm). The population in this study were students of BK a1 class of 2017 at PGRI AdiBuana University, Surabaya. The sample in this study used purposive sampling, namely there were 5 students who had the highest self harm score. The results of this study indicate that there is a decrease in the mean pre-test value of 64.60 to the mean post-test value of 53.40. So it can be concluded that the use of information services using imperfect films is significantly effective in reducing self harm.